Workers' Compensation Claims for Conditions Presumed to Be Occupational Diseases Among Firefighters in Washington State, 2000–2017. Issue 2 (17th February 2023) - LaSee, Claire R.; Bonauto, David K.; Marcum, Jennifer
Abstract : Occupational disease presumption laws for firefighters are common, yet there very little is known about firefighters who file claims for conditions presumed to be occupational diseases. This study characterizes claims filed by WA firefighters between 2002 and 2017 for conditions covered in the presumption law. Abstract : Objective: Occupational disease presumption laws for firefighters are common, yet little is known about the workers' compensation claims filed for them. Methods: We identified Washington State's workers' compensation claims for conditions covered by presumption among firefighters during 2000 to 2017, and described them by disease type and claim characteristics. Claim rates for specific cancers were compared with statewide incidence rates using the Washington State cancer registry. Results: Firefighters filed 330 claims for conditions covered by presumption (heart problems, 43%; cancer, 35%; respiratory disease, 15%; and infectious diseases, 8%), with acceptance rates varying by disease and insurer type. Cancer claims were associated with the highest claim costs and time loss. Conclusions: This study provides necessary baseline data to understand the impact of presumption laws on workers' compensation systems, and can inform future decisions presumption law expansions for firefighters.